PENERAPAN PRINSIP KEHATI-HATIAN PERBANKAN (PRUDENTIAL BANKING) DALAM PROSES PENYALURAN KREDIT PERBANKAN DI INDONESIA - Darwance Darwance (PROGRESIF: Jurnal Hukum, 2017)
As a financial institution which as intermediating function, bank has to re-distribute credits relied on collected funding from the people, thus the funding circle works properly. Article 2 Banking Law decrees that in applying duties Indonesian banking as based on Pancasila and Constitution of Republic of Indonesia 1945 of years by using orudent principal. Ignorance of prudential banking in credit distributional process contained in 5C principle and other well-known principles lead to the danger in the existence of banking industries